Pemenuhan Aspek Kepastian, Kemanfaatan, dan Keadilan Hukum dalam Sengketa Waris - Yusuf HR, Mohammad; Anam, Choirul (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
This study aimed to describe inheritance disputes and the fulfillment of aspects of certainty, utility, and legal justice in the District Court Decision Number 203/Pdt.G/2001/PN.Mlg and the Supreme Court Decision Number 2332K/Pdt/2003. This study used a normative legal method by conceptualizing a statutory regulation. This study was a qualitative descriptive study because it aimed to describe the Decision of the District Court Number 203/Pdt.G/2001/PN.Mlg and the Decision of the Supreme Court Number 2332K/Pdt/2003 systematically and accurately. Inheritance disputes in the District Court Decision Number 203/Pdt.G/2001/PN.Mlg and the Supreme Court Decision Number 2332K/Pdt/2003 were acts that aimed at controlling the inheritance without the knowledge of the heirs. The decision of the District Court Number 203/Pdt.G/2001/PN.Mlg did not reflect the aspects of certainty, utility, and legal justice. It did not pay attention to and considered Law Number 1 of 1974, the provisions of Article 118 paragraph (1) Herzien Inlandsch Reglement, and evidence from the defendants. The Supreme Court’s decision Number 2332K/Pdt/2003 reflected the aspects of certainty, benefit, and legal justice because it has taken into account and considered the facts and evidence in the trial in the form of a certificate from the inheritance hall as well as a copy of the Decree of the Religious Court Number 4026/1985.